The Risk Factors and Management of Neonatal Sepsis in A Tertiary Care Hospital in Bangladesh - Azam, Md Golam; Sufian, Abu; Mahmud, Ashik; Majumder, Simul; Parveen, Nilufa; Rana, Juwel; Amin, Ruhul (Eastern Medical College Journal, 2024)
Background: Despite significant attempts to mitigate its effects, still now in Bangladesh neonatal sepsis is regarded as a major cause of morbidity and mortality in newborns. The main goal of this study is to evaluate the risk factors and management of neonatal sepsis in a tertiary care hospital in Bangladesh. Materials & Methods: This cross-sectional study was carried out in Brahmanbaria medical college hospital, Brahmanbariawith ethical clearance from respective IERB. Hundreds (100) neonates with suspected neonatal sepsis who were admitted in the neonatal unit were included in this study. Clinical sepsis was diagnosed based on the presence of one or more of the following features:fever (≥38.0°C), hypothermia (≤36.5°C), convulsions, lethargy, poor feeding, respiratory distress, vomiting, bulging fontanels, jaundice and umbilical pus infections. Results: In this study 45 cases belong to 15-21 days and majority (60%) cases were female. While evaluating the hygiene status, 80 cases undergone poor hygiene status, followed by 70 cases had formula feeding and 40 cases had the history of prolonged labour, 35 cases had history of perinatal asphyxia. Extremely low birth weight occurred in 20% of cases, and low birth weight occurred in 40% of cases. Respiratory distress was seen in 70 cases followed by fever in 60 cases, hypothermia in 20 cases, convulsion in 20 cases, skin rash in 25 cases and jaundice in 20 cases. Most common organism was Streptococcus agalactia (40%) where 60% got their antibiotic treatment for 5-7 days. 60% of cases were discharged with advice. The mortality rate was only 20% in this study. Conclusion: In this study lethargy, respiratory distress and fever are typical clinical characteristics of newborn sepsis. Home delivery cases were found to be significant percentage along with prelacteal and formula feeding. Besides that, streptococcus agalactiae was found as a major isolated organism for progression of neonatal sepsis. This study emphasizes that advances in newborn intensive care medicine can be applied to increase sepsis survival. Eastern Med Coll J. July 2024; 9 (2): 100-104